Remainder & Factor Theorem - To understand and use Remainder Theorem to solve for unknowns and to find remainder (to carry

out long or synthetic division). - To use the Factor Theorem to find factors, solve for unknowns, find solutions to polynomial equations. When a polynomial P(x) is divided by (x – a) and gives a remainder of P(a), then this result is called the remainder theorem. If for a polynomial P(x) we find that P(a) = 0, we deduce from the remainder theorem that there is no remainder when P(x) is divided by (x – a). Thus we have the factor theorem, which states that If P(a) = 0 then (x – a) is a factor of polynomial. In the previous lesson, example (i) (x3 + 3x2 + 3x + 1) ÷ (x + 1) gives a remainder of 0, and so we say that (x + 1) is a factor of (x3 + 3x2 + 3x + 1). Factorize the following polynomials: (a) 6x3 + 13x2 - 4 (b) x4 - 16 (c) x3 - 2x2 + x - 2 (d) 2x4 + 7x3 - 4x2 - 27x - 18 (e) x4 + 5x3 + 6x2 - x - 2 More problems a) When the polynomial 4x4 - ax2 + 5x + 2 is divided by (2x - 1), the remainder is 4, find the value of a. a=3 b) When the polynomial f(x) = x5 + ax3 + ax + 4 is divided by ( x - 2 ) the remainder is 6. Find the remainder when it is divided by ( x + 2 ). Rem = 2 c) Show that ( x - 2 ) is a factor of the polynomial x 3 - 2x2 + x - 2 and find the other factor. x2 +1 d) If ( x2 - x - 6 ) is a factor of the polynomial x 4 + ax3 - 9x2 + bx -6, find the values of a and b. a = 3 and b = - 25
e)

(x + 2) (2x - 1) (3x + 2) (x - 2) (x + 2) (x2 + 4) (x - 2) (x2 + 1) (x - 2) (x + 3) (2x + 3) (x + 1) (x + 2) (x3 + 3x2 - 1)

Given that ( x2 - 1 ) is a factor of the polynomial f(x) = 3x4 + ax3 + bx2 7x - 4, find the values of a and b and hence factorize f(x) completely. a = 7 and b = 1; f(x) = (x - 1) (3x + 4) (x + 1) Given that ( x - 2 ) ( x + 2 ) are factors of x 3 + ax2 + bx + 4, find the values of a and b. a = -1 and b = - 4

f)

g) Show that ( x - 1 ) is a factor of 6x 3 + 11 x2 - 5x - 12, and find the other two linear factors of this equation. (x - 1) (3x + 4) (2x + 3)
h) Given that f(x) = ax3 + x2 - 4x + b, f(0) = 1 and f(1) = 0. Find the values

of a and b and factorize the resulting expression. a = 2, b = 1 ; (x - 1)(2x2 + 3x –1) i) Given that ( x - 1 ) is a factor of ax4 + 3x2 + x + b, and that the remainder when the function is divided by ( x + 2 ) is 21. find the values of the constants a and b. a = 1 and b = -5 j) If ( x2 - 4 ) is a factor of x 4 - 2x3 + ax2 + bx + 8, use the factor theorem to find two linear equations connecting a and b and hence find the values of these constants. a = - 6 and b = 8

Solving Polynomial Equations a) x3 + 3x2 + x - 1 = 0 b) √ ( 3 - x ) - √ ( 7 + x ) = 2 c) x3 - 5x2 - x + 5 = 0 d) x3 - 9x2 + 26x - 24 = 0 e) 2x3 + x2 - 13x + 6 = 0 -3 f) 4x3 + 8x2 + x - 3 = 0 3 2

x = -1 ± √2 x=-6 x = ± 1 or x = 5 x = 2, 3, 4 x = 2, ½ , x = ½ , or